LANGUAGE FOR LIVING: A PRINCIPLED APPROACH TO TEACHING MOTHER TONGUE - Doughty, Peter (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1979)
Probably the chief obstacle to plain sailing in English classrooms in these days is the inconsistency of principle manifest in the daily practice of many teachers. Peter Doughty points to the failure to recognize the fundamental differences between the language used every day for life and the specialized school variety that he calls "language for learning" as the cause of most of the confusion and consequent failure to achieve any real results with teaching. His frequent references to Language for Use, that landmark text of which he was co-author (that is not so widely used in Canada as it might be) are justified by its universally acknowledged and outstanding practicality. But without a grasp of certain principles of action, he is saying, no text is enough.